2015
DOI: 10.3389/fphys.2015.00213
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of dental pulp cell-based products from human third molars: current strategies and future investigations

Abstract: In recent years, mesenchymal cell-based products have been developed to improve surgical therapies aimed at repairing human tissues. In this context, the tooth has recently emerged as a valuable source of stem/progenitor cells for regenerating orofacial tissues, with easy access to pulp tissue and high differentiation potential of dental pulp mesenchymal cells. International guidelines now recommend the use of standardized procedures for cell isolation, storage and expansion in culture to ensure optimal reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 83 publications
(123 reference statements)
1
38
0
1
Order By: Relevance
“…A recent report [185] described manufacturing strategies of DPSC-based ATMPs to improve safety, efficacy, and consistency of their GMP production. The authors proposed the use of impacted third molars of young healthy donors between 5 and 7 Nolla's developmental stage (i.e., from complete crown upto one third of root completed) as ideal dental MSC sources.…”
Section: Establishment Of Clinical-grade Dental Mscs and Challengementioning
confidence: 99%
“…A recent report [185] described manufacturing strategies of DPSC-based ATMPs to improve safety, efficacy, and consistency of their GMP production. The authors proposed the use of impacted third molars of young healthy donors between 5 and 7 Nolla's developmental stage (i.e., from complete crown upto one third of root completed) as ideal dental MSC sources.…”
Section: Establishment Of Clinical-grade Dental Mscs and Challengementioning
confidence: 99%
“…Dental and craniofacial research currently explores a variety of cell-based and tissue engineering protocols to be used as alternatives to classical therapies that aimed at repairing/regenerating damaged tissues (Ducret et al, 2015a; Gorin et al, 2016). In particular, studies have demonstrated that mesenchymal stromal/stem cells (MSCs) are suitable to these protocols because of their high expansion ability and differentiation potential both in culture and animal models.…”
Section: Introductionmentioning
confidence: 99%
“…We recently isolated and easily amplified in culture a population of MSCs from the DP of human developing third molars with a medicinal manufacturing approach (Ducret et al, 2015b). We showed by using flow cytometry that all cells of this population expressed the mesenchymal cell markers CD10, CD13, CD29, CD44, CD90, CD105, and CD166 in vitro , but did not express the hematopoietic markers CD14, CD34, CD45, CD79a, and HLA-DR or the endothelial cell/leucocyte marker CD31 (Ducret et al, 2015a,b; Ducret et al, 2016). Stro-1 and CD271 were expressed by a very low number (≤ 1%) of cultured DP-MSCs, whereas CD146 and MSCA-1 were expressed by about 40 and 15% of DP-MSCs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Explant based isolation could also be easily adapted to xeno‐free isolation and expansion of DPSCs on a clinical scale, which would further simplify regulatory approvals (Ducret et al, ). Further expansion of cells derived by sustained explant technique showed identical surface marker profiles in all cultures, validating the MSC‐phenotype.…”
Section: Resultsmentioning
confidence: 99%